Analisis Peran Dompet Dhuafa Cirebon dalam Pengembangan Filantropi Islam - Della Wahyuningsih; Diva Nazmi Laila; M Daffa Dhiya Ulhaq; Mohammad Ridwan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe the role of Dompet Dhuafa Cirebon as a non-profit organization in developing Islamic philanthropy in the local area. Using a descriptive qualitative approach and case study, data were obtained through documentation from various sources such as official websites, activity reports, and news articles. The results of the study show that Dompet Dhuafa Cirebon runs various strategic programs such as Kampung Ternak, Tani Padu, Wakaf Sumur, Sewing Training for Dhuafa Widows, and Family-Friendly Homecoming Posts. These programs do not only focus on direct assistance, but also on empowering the community's economy and increasing social awareness. The philanthropic activities carried out reflect Islamic values ​​in helping others and utilizing digital technology to expand the reach of services. This study shows that the existence of philanthropic institutions such as Dompet Dhuafa has an important role in supporting community welfare and strengthening social solidarity based on Islamic values.